Evaluación del impacto de los programas de prevención y promoción de las enfermedades laborales en la industria manufacturera en Colombia. (2021)
The world health organization (WHO) establishes that occupational health is a multidisciplinary activity aimed at promoting and protecting the health of workers through the prevention and control of diseases and accidents, and with it the elimination of factors and conditions that endanger health and safety at work. In Colombia, the Ministry of Labor established the Occupational Health and Safety Management System (SG-SST) which must be implemented by all employers in order to anticipate, recognize, evaluate and control the risks that may affect the health and safety in the workplace.